Estimating the indirect prevalence of female genital mutilation/cutting in Switzerland - S. Cottler-Casanova; J. Abdulcadir (BMC, 2021)
Abstract Background We updated the indirect estimates for women and girls living with Female Genital Mutilation Cutting (FGM/C) in Switzerland, using data from the Swiss Federal Statistical Office of migrant women and girls born in one of the 30 high-prevalence FGM/C countries that are currently living in Switzerland. Methods We used Yoder and Van Baelen's "Extrapolation of FGM/C Countries' Prevalence Data" method, where we applied DHS and MICS prevalence figures from the 30 countries where FGM/C is practiced, and applied them to the immigrant women and girls living in Switzerland from the same 30 countries. Results In 2010, the estimated number of women and girls living with or at risk of FGM/C in Switzerland was 9059, whereas in 2018, we estimated that 21,706 women and girls were living with or at risk of FGM/C. Conclusion Over the past decade, there have been significant increases in the number of estimated women and girls living with or at risk of FGM/C in Switzerland due to the increase in the total number of women and girls originally coming form the countries where the practice of FGM/C is traditional.